2013
DOI: 10.1017/s1474748013000194
|View full text |Cite
|
Sign up to set email alerts
|

-theory of one-dimensional rings via pro-excision

Abstract: Link to this article: http://journals.cambridge.org/abstract_S1474748013000194 How to cite this article: Matthew Morrow (2014). -theory of one-dimensional rings via pro-excision .Abstract This paper studies 'pro-excision' for the K-theory of one-dimensional, usually semi-local, rings and its various applications. In particular, we prove Geller's conjecture for equal characteristic rings over a perfect field of finite characteristic, give results towards Geller's conjecture in mixed characteristic, and we estab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…The aim of this note is to explore certain analogues of this injectivity conjecture in the case when A is singular, by taking into account nilpotent thickenings of its singular locus. In the case that A is one-dimensional, this problem was first considered by the first author when n = 2 [6], and later by the second author in general [10]. In this note, we extend some of our earlier results to higher dimensions.…”
Section: Introductionsupporting
confidence: 60%
“…The aim of this note is to explore certain analogues of this injectivity conjecture in the case when A is singular, by taking into account nilpotent thickenings of its singular locus. In the case that A is one-dimensional, this problem was first considered by the first author when n = 2 [6], and later by the second author in general [10]. In this note, we extend some of our earlier results to higher dimensions.…”
Section: Introductionsupporting
confidence: 60%
“…Remark M. Morrow has recently demonstrated that the groups truelimiKn(boldZ/piboldZ) play an interesting role in a corrected Gersten conjecture for singular schemes. Although not in this paper, this suggests that they might play a role in future idèle theories , .…”
Section: Adèles With Quasi‐coherent Coefficientsmentioning
confidence: 69%
“…This provides a strengthening and purely algebraic proof of a result of Geisser and Hesselholt [14,Prop. 3.6], as promised in the author's earlier work [26,Lemma 1.12].…”
Section: The Equivalence Of Pro Unitality Conditionsmentioning
confidence: 85%
“…This has been previously proved by much longer arguments in the following two special cases: A is finitely generated over a characteristic zero field and A is assumed to be smooth, by Krishna [22, Thm. 1.1]; A is one-dimensional, by the author [26].…”
Section: Example 25 (Conductor Ideals) Letmentioning
confidence: 99%